Comparative evaluation of multiflower honey, jamun honey and chlorhexidine gluconate gel (0.2%) on clinical levels of dental plaque: one week Randomized controlled clinical trial. - GAUTAMI S PENMETSA,; L KALYANI KONDEPUDI, (International Journal of Pharma and Bio Sciences, 2017)
Honey produced by bees has been used as medicine since ages and in more recent times has been "rediscovered" indicating its potential in the treatment of inflammatory diseases like gingivitis. This study was intended to compare the effect of multiflower honey, jamun honey and chlorhexidine gluconate gel (0.2%) on clinical levels of dental plaque in patients with gingivitis. Ninety healthy patients aged between 18 to 50 years participated in the study and were randomly divided into three groups, i.e. the multiflower honey group, the jamun honey group and the chlorhexidine gluconate gel group. Once the Plaque index (PI), gingival index (GI) and bleeding index (BI) were recorded at baseline & 7th day, Statistical analysis was carried out using Paired t-test and one way ANOVA test. All the three groups showed statistically significant reduction in all the parameters except for plaque scores in jamun honey group, wherein significant reduction was not seen. The mean plaque scores for groups I, II, III on baseline and day7 were 4.08, 4.32, 4.50 and 3.60, 4.18, 4.22 respectively. There was a statistically significant difference with respect to reduction in BI scores amongst the three groups on day 7, while no statistically significant difference of PI, GI scores were evident. On the other hand both the honeys showed significant reduction of plaque and gingival indices similar to chlorhexidine gluconate gel. Hence the findings of this study elicit that honey can be used as a plaque control agent in patients with gingivitis.